ILCA 1993/94: Annual report and programme highlights - International Livestock Centre for Africa (International Livestock Centre for Africa, 1995)
This report highlights ILCA's work in the past, and discusses current activities and future plans with particular reference to mixed crop-livestock systems, market-oriented smallholder dairying, conservation of biodiversity, biological efficiency of livestock, livestock production under trypanosomiasis risk, livestock and resource management policy, and strengthening national research capacities.